A Base‐Stabilized Sila‐β‐Lactone and a Donor/Acceptor‐Stabilized Silanoic Acid1. Issue 34 (16th July 2013) - Rodriguez, Ricardo; Gau, David; Troadec, Thibault; Saffon‐Merceron, Nathalie; Branchadell, Vicenç; Baceiredo, Antoine; Kato, Tsuyoshi
<x xml:space="preserve">Abstract</x> A stable base‐stabilized sila‐β‐lactone was successfully synthesized and fully characterized. Interestingly, this sila‐β‐lactone shows a very unique reactivity toward ethanol, leading to the formation of an isolable donor/acceptor‐stabilized silanoic acid.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>